2020
DOI: 10.1002/em.22378
|View full text |Cite
|
Sign up to set email alerts
|

A review on the 40th anniversary of the first regulation of drinking water disinfection by‐products

Abstract: Water disinfection, primarily by chlorination, is one of the greatest achievements of public health. However, more than half a century after its introduction, studies in the 1970s reported that (a) chlorine interacted with organic matter in the water to form disinfection by‐products (DBPs); (b) two DBPs, chloroform and bromoform, both trihalomethanes (THMs), were rodent carcinogens; (c) three brominated THMs were mutagenic; in six studies chlorinated drinking waters in the United States and Canada were mutagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 97 publications
0
25
0
Order By: Relevance
“…Disinfecting drinking water from all surface water sources is a critical treatment step for protecting public health against disease‐causing waterborne pathogens (Schoenen, 2002). However, chemical disinfectants can react with naturally occurring material in the water to form DBPs, potentially posing significant human health risks (DeMarini, 2020; USEPA, 2006; Regli et al, 2015; Rook, 1974). Key factors influencing DBP formation include source water organic material composition and concentrations; source water pH and temperature; precursor removal rates; distribution system residence time; and the amount, timing, and type of disinfectant used during treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disinfecting drinking water from all surface water sources is a critical treatment step for protecting public health against disease‐causing waterborne pathogens (Schoenen, 2002). However, chemical disinfectants can react with naturally occurring material in the water to form DBPs, potentially posing significant human health risks (DeMarini, 2020; USEPA, 2006; Regli et al, 2015; Rook, 1974). Key factors influencing DBP formation include source water organic material composition and concentrations; source water pH and temperature; precursor removal rates; distribution system residence time; and the amount, timing, and type of disinfectant used during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown associations between the development of bladder cancer and exposures to both chlorinated drinking water (Cantor et al, 1985, 1998; King & Marrett, 1996; McGeehin et al, 1993; Villanueva et al, 2003) and DBPs (Cantor et al, 2010; DeMarini, 2020; Hrudey et al, 2015; Villanueva et al, 2004, 2007). Toxicity studies have also indicated DBPs can be carcinogenic and genotoxic (Richardson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…DBCM and bromoform were assigned to Group 3 Environmental Protection Agency (EPA) cancer potency factors because of their inconclusive carcinogenicity in humans and limited evidence from experimental studies on animals [ 1 , 8 ]. Besides carcinogenicity, animal studies indicate that chloroform in drinking water supplies may lead to low birth weight, prematurity, and intrauterine growth retardation [ 1 , 8 , 9 ]. Chloroform may cause acute and chronic ecological effects to aquatic life due to its moderate acute and chronic toxicity to aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The United States (U.S.) EPA has published the Disinfection By-products Rule to regulate total THMs at a maximum allowable annual average level of 80 ppb for Stage 1 and 40 ppb in Stage 2 for water treatment processes [ 9 ]. The maximum acceptable concentration (MAC) for THMs in drinking water established by Health Canada is 100 ppb.…”
Section: Introductionmentioning
confidence: 99%
“…Drinking water disinfected primarily by chlorine has been ubiquitous in most regions of the world for a century; however, the potential health effects of disinfection by‐products (DBPs), which are formed by the reaction of chlorine with organics and halides in the water, were not recognized until the 1970s (DeMarini, 2020). Among the >700 DBPs identified, >100 have been tested and found to be genotoxic in vitro, and 20 out of 22 that have been tested are carcinogenic in rodents (Richardson et al, 2007; Wagner and Plewa, 2017; Cortés and Marcos, 2018; DeMarini, 2020).…”
Section: Introductionmentioning
confidence: 99%